The Effect of Reduction Sugar of Heart Pineapple Extract and Saccharomyces cerevisiae Innoculant on Ethanol Fermentation - Wignyanto, Wignyanto; Suharjono, Suharjono; Novita, Novita (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
The experiment was aimed at studying waste of heart pineapple as a source of ethanol. Through fermentation process by Saccharomyces cerevisiae inoculants. The period of ethanol fermentation process is 4 days and observation did on every 24 hours. The variable observed ware; temperature, pH, ethanol concentration, reduction sugar concentration and the amount of Saccharomyces cerevisiae cell. Randomized block design with three replicated employed in this experiment. Treatment carried out were 1) initial concentration of reduction sugar of heart pineapple extract, 2) culture concentration and 3) fermentation period. Data analyzed with analysis variance BNJ test and regression analysis. This result showed interaction between initial concentration of reduction sugar and fermentation period. Have significantly effect to ethanol concentration, but culture concentration did not. The highest result is 30,30% ethanol concentration from treatment, 10% initial concentration reduction sugar and 4 days fermentation period and the lowest is 20,6% from treatment 14% initial concentration reduction sugar and 4 days fermentation period. Regression analysis showed reduction sugar concentration, the amount of Saccharomyces cerevisiae and ethanol concentration on media is interaction. Further to that, there were also an increase on the amount of Saccharomyces cerevisiae followed by decreasing reduction sugar concentration and increasing ethanol concentration on media. Acidity and temperature of medium tend to increase as long as fermentation period. Key word : Heart pineapple, ethanol